Analisis Efektivitas Penerapan Akad Ijarah pada Wakaf Produktif serta Dampak Ekonomi dan Sosial terhadap Masyarakat - Sugeng Riyadi; Amrizal; Yeni Oktoviani; Erni Juliana Al Hasanah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Productive waqf is a financial instrument that has great potential to improve community welfare. The application of the ijarah agreement in the context of productive waqf provides added value in managing waqf assets. This research aims to analyze the effectiveness of implementing the ijarah contract in productive waqf as well as the economic and social impact it has on society. The research design uses an associative qualitative approach, data is collected through surveys and interviews with waqf managers and beneficiary communities. The research results show that implementing the ijarah agreement can increase the productivity of waqf assets and have a positive impact on the community's economy. The implementation of the ijarah agreement has the potential to increase income and bring positive social change within the Yatim Mandiri Foundation. These findings are expected to contribute to waqf managers and policy makers in maximizing the benefits of waqf land for social and economic welfare